THE DEVELOPMENT OF INFORMATION-ANALYTICAL SUBSYSTEM OF ANALYSIS OF PUBLICATION ACTIVITY OF UNIVERSITY - Kcenia Nikolaevna Balastrova; Vasily Sergeyevich Kasyanov (Современная наука и инновации, 2022)
This article presents a conceptual framework for developing information-analytical system, allowing to monitor the publication activity. The urgency of the development of the system, as a means of solving problems of monitoring of the results of research activities and analytical processing of scientometric indicators and measurements. he proposals for the design of elements of the system developed.